Aplikasi Teknologi Aquaponic Pada Budidaya Ikan Air Tawar Untuk Optimalisasi Kapasitas Produksi - Nugroho, Ristiawan Agung; Pambudi, Lilik Teguh; Chilmawati, Diana; Haditomo, Alfabetian Herjuno Condro (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2012)
The experiment was conducted to acknowledge the effect of seed to the media using aquaponic system and to identify the influence of aquaponic system to the media’s water quality of Oreochromis niloticus’s fingerling to increase production capacity. The experiment was conducted at fish farmer’s fingerling ponds at Muntilan, Magelang (Central Java) for 2 weeks observations. It used completely randomized design, were reared at 200,400 and 600 fish density with three replications over to 2 m2 ponds with aquaponic system and 400 densities as a control to non-aquaponic system. The result of experiment showed that there was an influence of seed’s density to cultivan’s growth that used aquaponic system, especially to total length of fish. The aquaponic system is also influence the fixing of media water Oreochromis niloticus fingerling, especially the reduction of ammonias (NH3). Key words: aquaponic, water quality, red tilapia, fingerling